It's about minds, not marks - Abd Razak, Dzulkifli (2004)
By this week, thousands of new students will begin another phase in their lives as they step into campuses throughout the country. No doubt many will be wondering: How different is a university from their secondary schools? This is a valid question as much has been said on on what a university should be. So what is a university? The idea of a university has been discussed for years, and a consensus is still elusive. Partly, this is because different people perceive a university differently, especially those who own the university, governments included. In an autocratic society, for instance, the idea remains fuzzy because of the various limitations imposed on it. Some even have laws to ensure universities are "politically correct", in contrast to more open societies where a university is accorded independence (even though funded by the government).